Mucins in Lung Cancer. Issue 1 (January 2015) - Lakshmanan, Imayavaramban; Ponnusamy, Moorthy P.; Macha, Muzafar A.; Haridas, Dhanya; Majhi, Prabin Dhangada; Kaur, Sukhwinder; Jain, Maneesh; Batra, Surinder K.; Ganti, Apar Kishor
<x xml:space="preserve">Abstract</x> Aberrant expression of mucins is associated with cancer development and metastasis. An overexpression of few mucins contributes to oncogenesis by enhancing cancer cell growth and providing constitutive survival signals. This review focuses on the importance of mucins both in the normal bronchial epithelial cells and the malignant tumors of the lung and their contribution in the diagnosis and prognosis of lung cancer patients. During lung cancer progression, mucins either alone or through their interaction with many receptor tyrosine kinases mediate cell signals for growth and survival of cancer cells. Also, stage-specific expression of certain mucins, like MUC1, is associated with poor prognosis from lung cancer. Thus, mucins are emerging as attractive targets for developing novel therapeutic approaches for lung cancer. Several strategies targeting mucin expression and function are currently being investigated to control lung cancer progression.